Sedimentology and Morphology of Al-Rahaliyah Quarries Gravel,Al-Anbar Governorate, Central Iraq - Al-Dulaimi, Aliaa H.; Alhadaithy, Abdulhameed; Jasim, Hasan Kattoof (Iraqi Journal of Science, 2025)
The present study covers a sedimentological study of the gravel deposited in Al-Rahaliyah quarries for building materials in Al-Rahaliyah city within Al-Anbar Governorate. Ten samples of sediments were collected from ten sites, Dry sieving was done to separate the gravel fraction. A sedimentological analysis was performed on the gravel samples, covering the grain size fractions and morphology of gravel samples. The morphology included determining the form, roundness, and spherisity of these samples.The main size fraction of the studied gravel was pebbles (4-64mm), while the main form types were bladed and plated formTexturally the studied gravel sample of Al-Rahalyiah quarries is classified as Muddy Sandy Gravel and Sandy Gravel. About the shape of the studied gravels, the total average roundness of the studied samples is 4.2 (rounded), while the total average sphericity was 2.3 (Sub Discoidal). The roundness and sphericity of the studied gravels are affected by the fact that the original limestone rocks are deposited in horizontal sedimentary beds, and this stratification affected the shape of the studied gravels.The gravel was identified manually and using thin sections. It was found that the main lithology is carbonate type, while the type of carbonate rocks includes fossiliferous packstone, peloidal packstone, dolomitic limestone, and lithoclastic mudstone types, and the origin of these gravels are the Euphrates, Dammam, Anah, and Nfayil Formations, which are located in the west, and southwest related to the slope of the valleys in the study area.